2018
DOI: 10.3390/jcm7050110
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Pregnancy Rate Following Fallopian Tube Recanalization in Women with Proximal Fallopian Tube Obstruction

Abstract: Fallopian tube obstruction is a major cause of female infertility. We aimed to evaluate the factors potentially affecting pregnancy rate following fallopian tube recanalization (FTR) in infertile women with proximal fallopian tube obstruction. Data was retrospectively collected for 61 women (25, primary infertility; 36, secondary infertility) who underwent FTR at our institution. Bivariable and multivariable analyses of clinical pregnancy rates in relation to the following factors were performed: primary vs. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Regression analysis showed that short duration of infertility (less than 2 years) was significantly associated with spontaneous conception after 4D-HyCoSy, which was consistent with published studies [4]. The reason might be that long-term tubal obstruction caused by chronic inflammatory reaction damaged the internal structures including the cilia, and made it difficult to achieve spontaneous conception [21]. Therefore, we strongly recommend that infertile women should undergo 4D-HyCoSy examination as early as possible.…”
Section: Discussionsupporting
confidence: 86%
“…Regression analysis showed that short duration of infertility (less than 2 years) was significantly associated with spontaneous conception after 4D-HyCoSy, which was consistent with published studies [4]. The reason might be that long-term tubal obstruction caused by chronic inflammatory reaction damaged the internal structures including the cilia, and made it difficult to achieve spontaneous conception [21]. Therefore, we strongly recommend that infertile women should undergo 4D-HyCoSy examination as early as possible.…”
Section: Discussionsupporting
confidence: 86%
“…Some of these factors include the age of the patient, prior gynecology intervention, primary versus secondary infertility, and etiologies of infertility other than tubal factors. 10 In this study, secondary infertility cases appear to demonstrate higher spontaneous conception rates compared with those with primary infertility. This finding is explained by the notion that women who have had pregnancies in the past tend to have a higher incidence of fallopian tube occlusion and tend to have a higher chance of pregnancy once the underlying cause of infertility is addressed compared with their primary infertility counterparts.…”
Section: Discussionmentioning
confidence: 56%
“…The clinical data set is comparable to sample sizes in previous studies. 3 – 8 , 10 – 12 Furthermore, reporting of clinical outcomes of FTR across studies appears to be variable in that there are a staggering array of numerators and denominators used in the calculation of pregnancy rates. This may create variability in approaches to data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With proper techniques the average success rate post FTR alone rises up to approximately 30-35% and when utilized in combination to ARTs, significant surge in successful achieved conception or fertility are observed in state of art centers. 18,19 The complications following FTR are usually minor and major complications are very rare. The complications which may be seen in the patients undergoing FTR may include vascular contrast opacification due to forceful contrast injection or tight fibrotic blocks, fallopian tube perforation with no clinical manifestation, uterine or cervical mucosal erosion or injury and rarely uterine perforation.…”
Section: Discussionmentioning
confidence: 99%